Killer sperm whale: a new basal physeteroid (Mammalia, Cetacea) from the Late Miocene of Italy - Bianucci, Giovanni; Landini, Walter (Zoological Journal of the Linnean Society, 2006)
Bianucci, Giovanni, Landini, Walter (2006): Killer sperm whale: a new basal physeteroid (Mammalia, Cetacea) from the Late Miocene of Italy. Zoological Journal of the Linnean Society 148 (1): 103-131, DOI:10.1111/j.1096-3642.2006.00228.x, URL: https://academic.oup.com/zoolinnean/article-lookup/doi/10.1111/j.1096-3642.2006.00228.x